Trichoderma asperellum T42 Reprograms Tobacco for Enhanced Nitrogen Utilization Efficiency and Plant Growth When Fed with N Nutrients - Singh, Bansh N.; Dwivedi, Padmanabh; Sarma, Birinchi K.; Singh, Gopal S.; Singh, Harikesh B. (Frontiers in Plant Science, 2018)
Trichoderma spp., are saprophytitc fungi that can improve plant growth through increased nutrient acquisition and change in the root architecture. In the present study, we demonstrate that Trichoderma asperellum T42 mediate enhancement in host biomass, total nitrogen content, nitric oxide (NO) production and cytosolic Ca2+ accumulation in tobacco. T42 inoculation enhanced lateral root, root hair length, root hair density and root/shoot dry mass in tobacco under deprived nutrients condition. Interestingly, these growth attributes were further elevated in presence of T42 and supplementation of NO3- and NH4+ nutrients to tobacco at 40 and 70 days, particularly in NO3- supplementation, whereas no significant increment was observed in nia30 mutant. In addition, NO production was more in tobacco roots in T42 inoculated plants fed with NO3- nutrient confirming NO generation was dependent on NR pathway. NO3- dependent NO production contributed to increase in lateral root initiation, Ca2+ accumulation and activities of nitrate transporters in tobacco. Higher activities of several nitrate transporter genes in response to T42 and N nutrients and suppression of ammonium transporter (AMT1) suggested that induction of high affinity nitrate transporters help NO3- acquisition through roots of tobacco. Among the nitrate transporters NRT2.1 and NRT2.2 were more up-regulated compared to the other nitrate transporters. Addition of sodium nitroprusside (SNP), relative to those supplied with NO3-/NH4+ nutrition and T42 treated plants singly, and with application of NO inhibitor, cPTIO, confirmed the altered NO fluorescence intensity in tobacco roots. Our findings suggest that T42 promoted plant growth significantly ant N content in the tobacco plants grown under N nutrients, notably higher in NO3-, providing insight of the strategy for not only tobacco but probably for other crops as well to adapt to fluctuating nitrate availability in soil.